Double Jeopardy: Maintaining Livelihoods or Preserving Health? The Tough Choices Sex Workers Faced during the COVID-19 Pandemic - Martine Shareck; Maha Hassan; Pearl Buhariwala; Melissa Perri; Ermelina Balla; Patricia O'Campo (SAGE Publishing, 2021)
The COVID-19 pandemic and associated public health preventive measures such as lockdown and home confinement have posed unique challenges to female sex workers (FSW) globally, including in Canada where the sex trade is not formally recognized. In this commentary, we discuss the unintended consequences the pandemic has had on various social determinants of health among FSW. We draw on a review of scholarly and grey literature, complemented by our experience with the Exit Doors Here program, a sex work exiting program implemented in Toronto, Canada. Due to COVID-19, many FSW suddenly lost their main source of income, work conditions became riskier, and sheltering-in-place presented challenges for women with no safe housing. The slowdown of social and health care services also meant FSW were not receiving the required attention. We make recommendations for intersectoral mitigation strategies to limit the short- and long-term impacts of COVID-19 on FSW health and livelihoods. Recommendations focus on addressing women's marginalizing circumstances and speak to a gender transformative approach to the COVID-19 recovery. Our recommendations are relevant to FSW and other marginalized groups, in the current context and in the context of future health, social, and economic crises.